2A4 binds soluble and insoluble light chain aggregates from AL amyloidosis patients and promotes clearance of amyloid deposits by phagocytosis†. (2nd July 2016) - Renz, Mark; Torres, Ronald; Dolan, Philip J.; Tam, Stephen J.; Tapia, Jose R.; Li, Lauri; Salmans, Joshua R.; Barbour, Robin M.; Shughrue, Paul J.; Nijjar, Tarlochan; Schenk, Dale; Kinney, Gene G.; et al.
Abstract: Amyloid light chain (AL) amyloidosis is characterized by misfolded light chain (LC) (amyloid) deposition in various peripheral organs, leading to progressive dysfunction and death. There are no regulatory agency–approved treatments for AL amyloidosis, and none of the available standard of care approaches directly targets the LC protein that constitutes the amyloid. NEOD001, currently in late-stage clinical trials, is a conformation-specific, anti-LC antibody designed to specifically target misfolded LC aggregates and promote phagocytic clearance of AL amyloid deposits. The present study demonstrated that the monoclonal antibody 2A4, the murine form of NEOD001, binds to patient-derived soluble and insoluble LC aggregates and induces phagocytic clearance of AL amyloid in vitro . 2A4 specifically labeled all 21 fresh-frozen organ samples studied, which were derived from 10 patients representing both κ and λ LC amyloidosis subtypes. 2A4 immunoreactivity largely overlapped with thioflavin T–positive labeling, and 2A4 bound both soluble and insoluble LC aggregates extracted from patient tissue. Finally, 2A4 induced macrophage engagement and phagocytic clearance of AL amyloid deposits in vitro . These findings provide further evidence that 2A4/NEOD001 can effectively clear and remove human AL-amyloid from tissue and further support the rationale for the evaluation of NEOD001 in patients with AL amyloidosis.